TO THE MATTER OF STUDYING SHYNESS IN A CONTEXT OF STUDENTS' INTERCULTURAL ADJUSTMENT - G N Kameneva; M Radojev (Peoples' Friendship University of Russia (RUDN University), 2016)
The article considers the theoretical background for studying the conection between shyness as a personality trait and students' intercultural adjustment. One of the principal goals of the contemporary educational systems is to stimulate knowledge and cultural interchange and form a multicultural educational environment. The adjustment of foreign students to a new culture as well as to the educational process is realized through communication, therefore the personality traits related to social interaction are expected to give their contribution to this process. Shyness as a personality trait has been conceptualized mostly based on the western empirical research. Many neurological, physiological, psychological, social and cultural correlates have been brought to light. Among the contemporary lines of investigation on shyness it is important to emphasize the role of this feature in different social interactions and circumstances. Nevertheless, the association of shyness and the intercultural adjustment hasn't been considered in studies up to now. In the present article the authors tried to mark out the main points of contiguity of these two phenomena and ground the potential of this line of investigation.